La sacramentalidad del matrimonio: algunas notas desde la historia de la teología - Millán Romeral, Fernando (Estudios eclesiásticos, 2013)
This article focuses on the theological controversy over the sacramentality of marriage which took place at the Reformation (Luther, Henry VIII, Calvin and Trient). The author begins with the study of the subject in the thinking of the Church Fathers and medieval theology. There are two further developments of the subject: the application of the notion of sacrament to marriage in SC 59 und possible lines for ecumenical dialogue outlined in the Document of Venice (1976).